Hubungan Umur, Pekerjaan, Pendidikan dan Pendapatan terhadap Perilaku Orang Tua dalam Pemantauan Tumbuh Kembang Bayi Usia 0-1 Tahun pada Masa Pandemi Covid-19 - Ni Putu Riza Kurnia Indriana (Universitas Malahayati Lampung, 2022)
ABSTRACT Parents in compliance with monitoring growth and development are influenced by their education, age, level of knowledge, socioeconomic level, skills and intensity of interaction with health workers. Based on the 2013 Riskesdas data, 34.3% of parents did not monitor their growth and development, higher than in 2007 which was 25.5%. This shows that there are still many parents who have not monitored the growth and development of their children. Parents can monitor the baby's growth and development every month by taking the baby to the posyandu. During the Covid-19 pandemic, parents were reluctant to take their babies to the posyandu due to parental concerns about Covid 19. The purpose of this study was to analyze the relationship between age, occupation, education and income with parental behavior in monitoring the growth and development of infants aged 0-1 years during the Covid-19 pandemic. This research is a quantitative research with a cross sectional design. The research was conducted at UPTD. Health Center I of the South Denpasar District Health Office. The research sample is parents who come to the puskesmas with their babies aged 0-1 years to conduct an examination at the UPTD. Puskesmas I, Denpasar Selatan District Health Office, which met the inclusion and exclusion criteria. The sampling technique used convenience sampling with the number of samples calculated using a large sample formula of 95 respondents. The data collection tool was in the form of a questionnaire containing the identity of the respondents (age, education, occupation, monthly income as well as a questionnaire regarding the behavior of parents in monitoring the growth and development of aged infants). 0-1 years during the Covid 19 pandemic. Bivariate analysis using chi square. Based on the results of statistical analysis tests with the chi square test, it shows that there is a significant relationship between age of parents (p-value = 0.04), occupation (p-value = 0.000), education (p-value = 0.016) and income (p-value=0.013) of parents with parental behavior in monitoring the growth and development of infants aged 0-1 years during the Covid-19 pandemic. Age, occupation, education and income are related to the behavior of parents in monitoring the growth and development of infants aged 0-1 years during the Covid-19 pandemic. It is hoped that parents can monitor their child's growth and development every month at the posyandu in order to detect early developmental abnormalities. Keywords: Characteristics, Behavior, Growth and Development of Babies ABSTRAK Orang tua dalam kepatuhan melakukan pemantauan tumbuh kembang dipengaruhi oleh pendidikannya, umur, tingkat pengetahuan, tingkat sosial ekonomi, keterampilan dan intensitas interaksi dengan petugas kesehatan. Berdasarkan data Riskesdas 2013 terdapat 34,3% orang tua tidak melakukan pemantauan tumbuh kembang, lebih tinggi dari tahun 2007 sejumlah 25,5%. Hal ini menunjukkan masih banyak orang tua belum melakukan pemantauan tumbuh kembang anaknya. Pemantauan tumbuh kembang bayi dapat dilakukan orang tua setiap bulannya yaitu dengan mengajak bayinya ke posyandu. Selama masa pandemi Covid-19, orang tua enggan mengajak bayinya ke posyandu terkait adanya kehawatiran orang tua terhadap Covid-19. Tujuan penelitian ini untuk menganalisis hubungan umur, pekerjaan, pendidikan dan pendapatan dengan perilaku orang tua dalam pemantauan tumbuh kembang bayi usia 0-1 tahun selama masa pandemi Covid-19. Penelitian ini merupakan penelitian kuantitatif dengan desain cross sectional. Penelitian dilakukan di UPTD. Puskesmas I Dinas Kesehatan Kecamatan Denpasar Selatan. Sampel penelitian yaitu orang tua yang datang ke puskesmas bersama bayinya berumur 0-1 tahun untuk melakukan pemeriksaan di UPTD. Puskesmas I Dinas Kesehatan Kecamatan Denpasar Selatan yang memenuhi kriteria inklusi dan eksklusi. Teknik pengambilan sampel menggunakan convenience sampling dengan jumlah penghitungan sampel menggunakan rumus besar sampel sebanyak 95 responden. Alat pengumpulan data berupa kuesioner yang berisi tentang identitas responden (umur, pendidikan, pekerjaan, pendapatan per bulan serta kuesioner mengenai perilaku orang tua dalam pemantauan tumbuh kembang bayi usia 0-1 tahun pada masa pandemi Covid-19. Analisis bivariat menggunakan chi square. Berdasarkan hasil uji analisis statistik dengan uji chi square menunjukkan bahwa terdapat hubungan yang signifikan antara umur orang tua dengan (p-value=0.04), pekerjaan (p-value=0.000), pendidikan (p-value=0.016) dan pendapatan (p-value=0.013) orang tua dengan perilaku orang tua dalam pemantauan pertumbuhan dan perkembangan bayi usia 0-1 tahun pada masa pandemi Covid-19. umur, pekerjaan, pendidikan dan pendapatan berhubungan dengan perilaku orang tua dalam pemantauan pertumbuhan dan perkembangan bayi usia 0-1 tahun pada masa pandemi Covid-19. Diharapkan orang tua bisa memantau tumbuh kembang anaknya setiap bulan diposyandu guna mendeteksi secara dini timbulnya kelainan tumbuh kembang. Kata Kunci: Karakteristik, Perilaku, Tumbuh Kembang Bayi